The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1968
DOI: 10.1126/science.162.3861.1484
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cell Growth in vitro by Adenosine 3′,5′-Monophosphate

Abstract: Adenosine 3',5'-monophosphate, at a concentration of 40 micrograms per milliliter, inhibits the growth of HeLa and strain L cells in culture. The inhibition becomes progressively greater during the incubation of the cells. Adenosine 5'-monophosphate and adenosine, metabolites of adenosine 3',5'-monophosphate, do not affect the growth of either cell culture. This suggests that 3',5'-monophosphate enters the cell without alteration. Dibutyryl-adenosine 3',5'-monophosphate, reported to have a greater activity tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
1

Year Published

1969
1969
1993
1993

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(47 citation statements)
references
References 11 publications
1
45
1
Order By: Relevance
“…Thus, in skin c-AMP levels fluctuate with a pronounced diurnal rhythm, reaching a maximum during the resting phase of growth (Marks and Grimm, 1972). In vitro, c-AMP, dibutyryl cyclic AMP and ISOP also inhibit DNA synthesis in PHAand concanavalin A stimulated lymphocytes (Abell, Kamp and Johnson, 1970;Johnson and Abell, 1970;Krug et al, 1972) and the growth of HeLa and L cells (Ryan and Heidrick, 1968). Otten, Johnson and Pastan (1971) studied fibroblasts in logarithmic growth phase and growth of virus transformed 3T3 cells in vitro; they found that intracellular levels of c-AMP were inversely proportional to DNA synthesis.…”
Section: -Hydroxytryptamine (50h-t)mentioning
confidence: 99%
“…Thus, in skin c-AMP levels fluctuate with a pronounced diurnal rhythm, reaching a maximum during the resting phase of growth (Marks and Grimm, 1972). In vitro, c-AMP, dibutyryl cyclic AMP and ISOP also inhibit DNA synthesis in PHAand concanavalin A stimulated lymphocytes (Abell, Kamp and Johnson, 1970;Johnson and Abell, 1970;Krug et al, 1972) and the growth of HeLa and L cells (Ryan and Heidrick, 1968). Otten, Johnson and Pastan (1971) studied fibroblasts in logarithmic growth phase and growth of virus transformed 3T3 cells in vitro; they found that intracellular levels of c-AMP were inversely proportional to DNA synthesis.…”
Section: -Hydroxytryptamine (50h-t)mentioning
confidence: 99%
“…In vitro, exogenous cGMP stimulates the proliferation of fibroblasts and lymphoid cells Whitfield et al, 1971;Diamantstein & Ulmer, 1975;Watson, 1975) whereas cAMP, or agents which increase its intracellular concentration, inhibit cell growth (Ryan & Heidrick, 1968;Yang & Vas, 1971;Pardee, 1974) and induce in malignant cells a normalappearing morphological or biochemical differentiation (Hsie & Puck, 1971;Johnson et al, 1971;Prasad et al, 1975).…”
mentioning
confidence: 99%
“…2B) Bt2cAMP (18-21; B. E. Ledford and J. Papaconstantinou, manuscript in preparation). In addition, intracellular cAMP levels have been shown to increase with cell density (22)(23)(24). In view of the above, cultures were treated with Btt2cAMP to determine whether the generation time of the FLC is altered and whether this, in turn, is reflected in the time of appearance of hemoglobin.…”
mentioning
confidence: 99%